Technology as a tool in teaching quantitative biology at the secondary and undergraduate levels: a review. Issue 1 (14th December 2018) - Chen, Miranda M.; Scott, S. M.; Stevens, Jessica D.
Abstract: Since the publication of the National Research Council's Report BIO2010, efforts have increased to better integrate mathematics and biology in undergraduate education. Unfortunately, equivalent efforts to introduce these quantitative topics at the secondary level have been seldom. This could cause differential success of undergraduate students who come from diverse secondary science backgrounds. Undergraduate courses regularly use technology to integrate these two disciplines, and we believe that technology can similarly be used at the secondary level to prevent quantitative achievement mismatch in undergraduate biology programmes. In this paper, we review the current uses of technology to teach quantitative biology at the secondary and undergraduate levels, propose needs for further implementation, and address potential barriers to integrating mathematics and biology using technology.